Teaching, organization, and personal problems: Evidence from reforming tertiary education in Germany - Andrea M. Mühlenweg (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Germany has recently made extensive reforms in its tertiary education system. Traditional degrees are being replaced by Bachelor and Master programs. This study examines the question of how the choice of a new Bachelor program as opposed to a traditional degree program has affected first-year students' satisfaction. Three dimensions of student satisfaction are focused upon: Student satisfaction with teaching, student satisfaction with the organization of the study programs, as well as an indicator for students' personal problems within the academic context. The selection into the type of program is taken into account as I control for individual performance at secondary school, motivation and family background and try different robustness checks. The main specification includes fixed effects on the level of institutions and subjects. Results robustly point to minor differences between the programs. The outcomes are slightly more favorable for students in the new programs compared to the traditional programs in recent years.
Keywords: I21; I28; 330; Bologna; reforms; evaluation; fixed effects; student satisfaction; Hochschulreform; Wirkungsanalyse; Studierende; Arbeitszufriedenheit; Lebenszufriedenheit; Deutschland